Microsatellite markers for the Jaera albifrons species complex (marine isopods) - Ribardière, Ambre; Broquet, Thomas; Daguin-Thiébaut, Claire (BMC Research Notes, 2015)
International audience Background: The Jaera albifrons complex contains five species of marine isopods (J. albifrons, J. praehirsuta, J. ischio-setosa, J. forsmani, and J. posthirsuta). These species, occurring on the shores of the North‑Atlantic Ocean, are partially reproductively isolated by barriers due to sexual isolation (mate choice), genetic incompatibilities, and ecological spe‑ cialization. Microsatellite loci would be useful for parentage‑based analyses of sexual selection and studies of genetic structure in the context of speciation. Findings: Twenty‑four microsatellite markers were developed for J. albifrons using pyrosequencing of enriched libraries. Patterns of polymorphisms were analyzed in 49 J. albifrons adult males sampled in two populations from Brittany (Western France). The average number of alleles per locus was 4.73 ± 2.45 and the average gene diversity was 0.55 ± 0.23. Most markers also successfully amplified in the three sibling species J. praehirsuta, J. ischiosetosa, and J. forsmani. Conclusions: These polymorphic and cross‑amplifiable markers will be useful for population genetics and parentage studies in the J albifrons complex.